Distribuição especial dos Annelida - Polychaeta em substratos não consolidados do Saco do Céu - Ilha Grande - Angra dos Reis - RJ - Brasil, Ana Claúdia dos Santos (1995)
The main purpose of this study was to determine the spatial distribution of Annelida Polychaeta in Saco do Céu - Ilha Grande - Angra dos Reis - Rio de Janeiro, an inlet facing the continent. Thirty-nine stations were done in two different periods of the year (January and July/1992). A 0,1 m2 Petersen grab was used to collect the biological material and the sediment for granulometric analysis. The bottons of the studied area formed a mosaic which varied from fine to very coarse sand. The main species found were: Glycinde multidens, Sigambra grubii, Paraprionospio pinnata, Cirrophorus branchiatus, Laonice branchiata, Prionospio (M.) cirrifera, Magelona papíllicornis, Mediomastus californiensis, Armandia agilis, Gyptis capensis e Goniadides carolinae , and their distribution was determined by the sediment type at each place. No difference concerning fauna, types of sediment and even diversity was faund in relation to both periods of year, and the spatial distribution of Polychaeta was determined by grain - size characteristics and by the contents of organic matter.